2007
DOI: 10.1080/01421590701294323
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of peer, self, and tutor assessment in problem-based learning tutorials

Abstract: According to the results of this study, first-year medical students in a problem-based learning curriculum were better able to accurately judge the performance of their peers compared to their own performance. This study has shown that self-assessment of process is not an accurate measure, in line with the majority of research in this domain. Nevertheless, it has an important role to play in supporting the development of skills in reflection and self-awareness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
113
0
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 143 publications
(138 citation statements)
references
References 50 publications
12
113
0
8
Order By: Relevance
“…These authors conclude that the correlation between an actual and an estimated score is not a very useful indicator of SA accuracy because it quantifies an aspect that is distinct from those summarized in the bias and deviation measures. In one of the few studies conducted in accounting education, Larres, Ballantine and Whittington (2003) Other studies have assessed the accuracy of both SA and PA compared to TA by means of correlation coefficients (e.g., Longhurst and Norton, 1997;Papinczak et al, 2007;Lew, Alwis and Schmidt, 2010) but have not always found it to be a very useful indicator for accuracy 6 (Fitzgerald, White and Gruppen, 2003). For example, Longhurst and Norton (1997) compare SA to TA for second-year undergraduate psychology students; they find a significant positive correlation (r = 0.43) between student and tutor grades.…”
Section: Self-and Peer-assessmentmentioning
confidence: 99%
See 4 more Smart Citations
“…These authors conclude that the correlation between an actual and an estimated score is not a very useful indicator of SA accuracy because it quantifies an aspect that is distinct from those summarized in the bias and deviation measures. In one of the few studies conducted in accounting education, Larres, Ballantine and Whittington (2003) Other studies have assessed the accuracy of both SA and PA compared to TA by means of correlation coefficients (e.g., Longhurst and Norton, 1997;Papinczak et al, 2007;Lew, Alwis and Schmidt, 2010) but have not always found it to be a very useful indicator for accuracy 6 (Fitzgerald, White and Gruppen, 2003). For example, Longhurst and Norton (1997) compare SA to TA for second-year undergraduate psychology students; they find a significant positive correlation (r = 0.43) between student and tutor grades.…”
Section: Self-and Peer-assessmentmentioning
confidence: 99%
“…Longhurst and Norton (1997) conclude that students are reasonably accurate at grading their own essays although the magnitude of the correlation coefficient obtained is lower than 0.50. Papinczak et al (2007) also explore the accuracy of SA and PA relative to TA for first-year medical students using the Pearson correlation coefficient.…”
Section: Self-and Peer-assessmentmentioning
confidence: 99%
See 3 more Smart Citations